DYNAMICS OF ROTOR SYSTEM SPATIAL MOTION IN DYNAMIC DIAGNOSTICS - Mikhail V. Chuveyko (Вестник Донского государственного технического университета, 2018)
The application of the quaternion kinematics for building a mathematical model of the rotor system engaged in three-dimensional motion is considered.